Perbandingan Hasil Performa Optimasi Transposisi Hill Cipher dan Vigenere Cipher pada Citra Digital - Bayu Firmanto; Devita Putri Kusuma Ningrum; Arief Bramanto Wicaksono Putra (Universitas PGRI Kanjuruhan Malang, 2021)
The security system is one of the crucial factors in sending data. Cryptography is a security system with a working system that converts data into passwords that are difficult to understand. This studycompares the results of the transposition optimization performance on the classic algorithm, Hill Cipher andVigenere Cipher. This research aims to find out the best algorithm suitable for the transposition technique and improve the image encryption results. Optimization performance is assessed visually and tested using the Discrete Cosine Transform (DCT) method, then testing the encrypted image using the MSE methods. Thisstudy used three image samples with PNG format measuring 200 * 200 and 220 * 220 pixels. The average value in the first image sample of the original Hill Cipher algorithm and with transposition optimization is 24.79% and 24.77%. The original Vigenere Cipher algorithm and transposition optimization, respectively, are 26.54% and 26.75% in the image. It shows that transposition optimization is more suitable to combine with the Vigenere Cipher algorithm because randomness increases.